Professional development program to promote students’ conceptual understanding through technology-enhanced teaching: a learner-centered evaluation - Digel, Susanne; Roth, Jürgen (Frontiers in Psychology, 2025)
IntroductionThe digital transformation of schools is currently in progress; yet, the beneficial utilization of technology-enhanced teaching (TET) for students’ learning remains an intricate endeavor. Teachers report a lack of skills in integrating technology to support learning and call for teacher professional development programs (TPDPs) and best practice materials. This paper outlines the concept and evaluation design of the TPDP MaTeGnu for upper secondary schools. MaTeGnu aims to exploit the potential of technology for instructional quality to support students’ conceptual learning with a focus on basic mental models. Based on a research synthesis on influential factors of TPDPs we formulate a TPDP model to facilitate the crucial transfer process from TPDP offer to teaching and thereof discuss the alignment of the MaTeGnu design with the model.MethodsThe present study aims to evaluate the MaTeGnu TPDP concept by assessing the students’ understanding, as central objective of the project. This evaluation employs an experimental-vs.-control-group design, which involves a comparison of the utilization of basic mental models (BMM) and the conceptual understanding of students regarding the concept of derivatives in classes, where teachers participate in MaTeGnu TPDP (NEG = 151) and in other classes at the respective schools (NCG = 571).ResultsStudents from MaTeGnu teacher educator classes demonstrate significantly higher conceptual understanding [t(225) = 3.78, p < 0.001, d = 0.346] and utilization of basic mental models, particularly of local rate of change [t(267) = 5.17, p < 0.001, d = 0.474], compared to other students.DiscussionThe findings at the most distant impact level of TPDP reveal noteworthy empirical evidence of the efficacy of the MaTeGnu approach of TET with BMM, particularly the accompanying transfer support, as outlined in our proposed TPDP transfer process model. The emphasis on BMM could provide an effective strategy to implement TET beneficial for learning, even in the more formal setting of upper secondary school mathematics.